Quantum technology a tool for sequencing of the ratio DSS/DNA modifications for the development of new DNA-binding proteins. Issue 1 (31st December 2022) - Ugya, Adamu Yunusa; Meguellati, Kamel
ABSTRACT: The current study summarizes the literature on quantum-based structural sequencing methods and their predicted roles in the discovery of new DNA-binding protein domains. Although there is no literature yet showing the role of quantum structural sequencing for the discovery of new domains for DNA-binding proteins, the current study shows that the development of new quantum-based and far-from-equilibrium biological systems can be achieved by 3D-curved room-temperature superconductivity materials. The technology is useful for protein engineering and 3D sequencing of the ratio DNA/RNA secondary structures (DSS)/Physiological Modifications (PM) and will overcome the use of nanopore and ChiP sequencing. This approach is very useful for the protein engineering of recombinant enzymes for the unnatural replication of proteins and glycans for new biochemical activities, treatment of HIV and cancers, new genome editing machinery, artificial replication and translation, first sequencing of DSS/physiological modification/telomere with a correlation to cancer genesis and therapy, The key DSS in this study are: quadruplex, hairpin loop, triplexes and duplexes, i-motif, Holliday junction; and the PM investigated: 6 mA, 6fmA, 5mC, 5fC, 8-oxo-guanine. The DSS/PM ratio is critical for proto-oncogene activation and cancer genesis.